2014
DOI: 10.1111/cge.12540
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of incidental findings in cancer genomic research: investigators' perceptions on obligations and barriers

Abstract: Although there has been significant research surrounding incidental findings (IFs), the guidelines and information provided to investigators remain unspecific, unclear, and often generalize the course of action to everyone in the field. We explored the perceptions and experiences of investigators regarding the return of IFs in genetic research. Researchers and clinician-researchers were invited to participate in semi-structured telephone interviews in Quebec and Ontario. Twenty professionals participated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Most researchers agreed that participants have a “right” to their data and that researchers have an ethical obligation to align return practices with participants' preferences. These findings support other studies of stakeholder's perspectives about RoR in genetics research generally (Kleiderman et al, ; Klitzman et al, ; Middleton et al, ). According to studies examining attitudes toward RoR in psychiatric genetics in particular (Sundby et al, ), stakeholders favored the return of both pertinent and incidental findings to individual research participants, mirroring opinions of our researcher respondents.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most researchers agreed that participants have a “right” to their data and that researchers have an ethical obligation to align return practices with participants' preferences. These findings support other studies of stakeholder's perspectives about RoR in genetics research generally (Kleiderman et al, ; Klitzman et al, ; Middleton et al, ). According to studies examining attitudes toward RoR in psychiatric genetics in particular (Sundby et al, ), stakeholders favored the return of both pertinent and incidental findings to individual research participants, mirroring opinions of our researcher respondents.…”
Section: Discussionsupporting
confidence: 88%
“…Another study found that 74% of a general public sample would like to receive genetics research results if they participated in a study (Kaufman, Baker, Milner, Devaney, & Hudson, ). A qualitative study by Kleiderman et al () suggested that genetics researchers believe a “one‐size‐fits‐all” approach to returning incidental findings is inappropriate and that context needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…5 Guidelines exist to help direct discussions on germline genetic testing 6 ; however, with the exception of incidental findings (IFs) directives, there are no established guidelines for informational and results-oriented discussions about tumor molecular testing. [7][8][9][10][11][12][13] For example, in the recently updated American Society of Clinical Oncology (ASCO) guidelines for genetic and genomic testing for cancer susceptibility, 14 the discussion of somatic molecular testing focuses on the discovery of incidental hereditary findings. Guideline development committees usually consist of experts, physicians, stakeholders, and patient advocates.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, considerations which have been previously raised regarding the return of results include: benefit to research participants if the findings are not clinically valid or actionable, 27,28 health care providers not being sufficiently trained for the disclosure 29 and infrastructure requirements and costs. 30,31…”
Section: Discussionmentioning
confidence: 99%